Genotypic and phenotypic heterogeneity among Chinese pediatric genetic white matter disorders - Liling Dong; Li Shang; Caiyan Liu; Chenhui Mao; Xinying Huang; Shanshan Chu; Bin Peng; Liying Cui; Jing Gao (BMC, 2023)
Abstract Background The pediatric genetic white matter disorders are characterized by a broad disease spectrum. Genetic testing is valuable in the diagnosis. However, there are few studies on the clinical and genetic spectrum of Chinese pediatric genetic white matter disorders. Methods The participants were enrolled from the cohort of Peking Union Medical College Hospital. They all received history collection, brain MRI and gene sequencing. Their neurologic complaints which were related to white matter disorders occurred before 18. Brain MRI indicated periventricular and/or deep white matter lesions, fazekas grade 2-3. Results Among the 13 subjects, there were 11 males and two females. The average age of onset was 10.0 ± 5.5 years old. The potential genetic variants were found in 84.6% (11/13) subjects. The ABCD1 showed the greatest mutation frequency (30.8%, 4/13). The EIF2B3 A151fs, EIF2B4 c.885 + 2T > G, EIF2B5 R129X and MPV17 Q142X were novel pathogenic/likely pathogenic variants. 100% (4/4) ABCD1 carriers were accompanied by visual impairment, whereas 100% (3/3) EIF2B carriers developed dysuria. 100% (4/4) ABCD1 carriers exhibited diffuse white matter hyperintensities mainly in the posterior cortical regions, while the EIF2B4 and EIF2B5 carriers were accompanied by cystic degeneration. Conclusion There is genotypic and phenotypic heterogeneity among Chinese subjects with pediatric genetic white matter disorders. The knowledge of these clinical and genetic characteristics facilitates an accurate diagnosis of these diseases.